Excessive Use of Deadly Force by Police in the Philippines Before Duterte. Issue 4 (8th August 2018) - Kreuzer, Peter
ABSTRACT: Under President Duterte the Philippine National Police have killed several thousand suspects in so-called legitimate encounters. While this has engendered much media attention and scientific research, earlier police violence is still a black-box in many respects. This article provides at least a partial filling of this void. It establishes several indicators for measuring lethal police violence. Moreover, it presents a detailed mapping of regional and sub-regional patterns of armed police encounters for the decade from 2006 to 2015. The spatial and temporal comparisons show that even though actual levels of deadly police violence have been quite low in several Philippine provinces and cities, the Philippine National Police almost always shot to kill suspects and not to incapacitate them. While there was significant variation over time and between sub-national units, neither the magnitude nor the levels of lethality of the violence are related to the threat levels to which the police officers were exposed.